The Roles of Manual and non-manual Cues in Recognizing Irony in Italian Sign Language. (2nd October 2022) - Giustolisi, Beatrice; Mantovan, Lara; Panzeri, Francesca
ABSTRACT: In a previous study, our research group investigated the expression of irony in Italian Sign Language (LIS) and suggested that specific manual and non-manual markers signaled the signer's meaning and attitude. The present research aimed at expanding those findings by analyzing whether these markers are used in irony recognition and whether they are language-specific. We designed an experiment in which we compared recognition of ironic remarks out of context considering three groups of Italians: Deaf signers, hearing signers, and hearing non-signers. Our aim was to verify whether the manual and non-manual markers we associated with the expression of irony in LIS constitute a reliable cue to detect irony and whether these cues were accessible to signers more than to non-signers sharing the same cultural background. Although the ironic intent in LIS was accessible also to hearing non-signers, we found, among hearing participants, that knowledge of LIS does improve accuracy in recognizing ironic remarks in LIS. This suggests that signers' facial expressions and bodily movements do not solve a purely affective function, but are grammaticalized, at least to some degree.